2007
DOI: 10.1111/j.1556-4029.2007.00566.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Histomorphological Features of the Sternal End of the Fourth Rib for Age Estimation in Koreans*

Abstract: The aim of this study was to assess the histomorphological features of the fourth rib and to develop age-predicting equations for Koreans. Sixty-four rib samples (36 males and 28 females) obtained from forensic cases were used for developing equations. Two thin sections (<100-microm thick) per sample were prepared by manual grinding. Multivariate analysis of covariance revealed statistically significant differences in age-adjusted histomorphological variables between sexes. Using stepwise regression analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
54
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 25 publications
(43 reference statements)
10
54
0
1
Order By: Relevance
“…The validation sample within that study demonstrates that the error associated with the development sample is consistent with prior studies (Stout and Paine 1992), with a predictive interval of ±24.44 years (Cho et al, 2002). This method strongly supports a population approach to histological age‐estimation largely based on ancestry, and the variables used form the basis for more recent population specific histological age‐estimation methods (Kim et al, 2007; Pavón et al, 2010; Cannet et al, 2011). An assessment by Crowder (2005) using 215 samples derived from the known age‐at‐death Spitalfields skeletal collection found that the histological age‐estimation method developed by Cho et al (2002) accurately estimated ages within the predicted interval.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…The validation sample within that study demonstrates that the error associated with the development sample is consistent with prior studies (Stout and Paine 1992), with a predictive interval of ±24.44 years (Cho et al, 2002). This method strongly supports a population approach to histological age‐estimation largely based on ancestry, and the variables used form the basis for more recent population specific histological age‐estimation methods (Kim et al, 2007; Pavón et al, 2010; Cannet et al, 2011). An assessment by Crowder (2005) using 215 samples derived from the known age‐at‐death Spitalfields skeletal collection found that the histological age‐estimation method developed by Cho et al (2002) accurately estimated ages within the predicted interval.…”
supporting
confidence: 59%
“…Current approaches to histological age‐estimation are largely based on the methods developed by Cho et al (Crowder et al, 2009; Cho et al, 2002; Kim et al, 2007; Pavón et al, 2010). It is often used as an exemplar in biological anthropology reference texts (Robling and Stout, 2008; Crowder, 2009; Crowder and Stout, 2012; Streeter, 2012).…”
mentioning
confidence: 99%
“…1/3 of the rib length, counting from the sternal end. The location lies on the boundary indicated by Stout and Paine (1992), Cho et al (2002) and Bednarek et al (2009), which is the middle 1/3 of the rib, and the spot indicated by Kim et al (2007), i.e. the sternal end of the rib.…”
Section: Methodsmentioning
confidence: 99%
“…This was achieved by preparing a microscopy sample in the form of a ground section of the analysed bone. Kerley's discovery inspired numerous researchers who expanded their investigations with an analysis of other bones, determined new indicators and modified the assessment methodology itself (Singh and Gunberg 1970;Ericksen 1991;Stout and Paine 1992;Cho et al 2002;Kim et al 2007;Bednarek et al 2009;Cannet et al 2011). As a result, many different formulas have been found that enabled age at death assessment based on the histomorphometry of the cortical bone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation